Genomic structure, ecological suitability and biogeographic history of the palm Acrocomia aculeata across Central America - Morales-Marroquín, Jonathan A.; López de Paz, Erick René; Silva-Rivera, Rocío; Francisconi, Ana Flávia; Orellana-Hernandez, Roger Alejandro; Palacios, José M.; Araya-Valverde, Emmanuel; Arnáez−Serrano, Elizabeth; Rabelo-Araujo, João Victor da Silva; Garcia, Caroline Bertocco; Scaketti, Matheus; Colombo, Carlos A.; et al. (Frontiers in Plant Science, 2026)
Central America is an understudied global hotspot of plant biodiversity and harbors Acrocomia aculeata (Coyol or Macaúba), a neotropical palm with significant potential for oil and biofuel production. Historically, the region has functioned as a biogeographic land bridge, an isthmus, connecting North and South American biota. Here, we investigate how genomic diversity and potential distribution patterns of A. aculeata are shaped across Central America. A total of 259 samples were collected from Guatemala, Honduras, Nicaragua, Costa Rica, and Panama, covering the full extent of the Central American isthmus. Using a double-digest genotyping-by-sequencing (ddGBS) approach and ecological niche modeling, we assessed variation at 1,523 single nucleotide polymorphisms (SNPs) and evaluated environmental suitability across the region. Our analyses reveal three major genomic clusters: Mesoamerican, Costa Rican, and Panamanian, each comprising subpopulations with distinct levels of genetic diversity. The Mesoamerican group (Guatemala, Honduras, and northern Nicaragua) exhibited the highest diversity and unique genetic signatures, likely reflecting historical migrations and acting as a biodiversity cradle during periods when southern portions of the isthmus were submerged. Biogeographic features such as the Nicaraguan Depression and the Talamanca Cordillera contributed to regional genetic differentiation. Ecological niche models identified Central American pacific lowlands, forested areas, rangelands, and agroecosystems as suitable habitats for A. aculeata. Our combined results reflect the evolutionary history and population structure of A. aculeata in Central America, highlighting the influence of South American source populations and regional barriers. These findings provide a critical foundation for conservation and breeding programs aiming to preserve the genetic diversity and adaptive potential of A. aculeata in a rapidly changing and neglected biodiversity hotspot.